Host cell nucleolin is required to maintain the architecture of human cytomegalovirus replication compartments - Strang, Blair L.; Boulant, Steeve (mBio, 2012)
Drastic reorganization of the nucleus is a hallmark of herpesvirus replication. This reorganization includes the formation of viral replication compartments, the subnuclear structures in which the viral DNA genome is replicated. The architecture of replication compartments is poorly understood. However, recent work with human cytomegalovirus (HCMV) showed that the viral DNA polymerase subunit UL44 concentrates and viral DNA synthesis occurs at the periphery of these compartments. Any cellular factors involved in replication compartment architecture are largely unknown. Previously, we found that nucleolin, a major protein component of nucleoli, associates with HCMV UL44 in infected cells and is required for efficient viral DNA synthesis. Here, we show that nucleolin binds to purified UL44. Confocal immunofluorescence analysis demonstrated colocalization of nucleolin with UL44 at the periphery of replication compartments. Pharmacological inhibition of viral DNA synthesis prevented the formation of replication compartments but did not abrogate association of UL44 and nucleolin. Thus, association of UL44 and nucleolin is unlikely to be a nonspecific effect related to development of replication compartments. No detectable colocalization of 5-ethynyl-2′-deoxyuridine (EdU)-labeled viral DNA with nucleolin was observed, suggesting that nucleolin is not directly involved in viral DNA synthesis. Small interfering RNA (siRNA)-mediated knockdown of nucleolin caused improper localization of UL44 and a defect in EdU incorporation into viral DNA. We propose a model in which nucleolin anchors UL44 at the periphery of replication compartments to maintain their architecture and promote viral DNA synthesis. IMPORTANCE Human cytomegalovirus (HCMV) is an important human pathogen. HCMV infection causes considerable rearrangement of the structure of the nucleus, largely due to the formation of viral replication compartments within the nucleus. Within these compartments, the virus replicates its DNA genome. We previously demonstrated that nucleolin is required for efficient viral DNA synthesis and now find that the nucleolar protein nucleolin interacts with a subunit of the viral DNA polymerase, UL44, specifically at the periphery of replication compartments. Moreover, we find that nucleolin is required to properly localize UL44 at this region. Nucleolin is, therefore, involved in the organization of proteins within replication compartments. This, to our knowledge, is the first report identifying a cellular protein required for maintaining replication compartment architecture.